Further observations on clinical, histopathological, and immunological features of borderline disseminated cutaneous leishmaniasis caused by Leishmania (Leishmania) amazonensis - SILVEIRA, Fernando Tobias (2013)
Leishmania (Leishmania) amazonensis has for some time been considered as the causative agent of two distinct forms of American cutaneous leishmaniasis (ACL): localized cutaneous leishmaniasis (LCL), and anergic diffuse cutaneous leishmaniasis (ADCL). Recently, a new intermediate form of disease, borderline disseminated cutaneous leishmaniasis (BDCL), was introduced into the clinical spectrum of ACL caused by this parasite, and in this paper we record the clinical, histopathological, and immunological features of eight more BDCL patients from Brazilian Amazonia, who acquired the disease in the Pará state, North Brazil. Seven of them had infections of one to two years' evolution and presented with primary skin lesions and the occurrence of metastases at periods varying from six to 12 months following appearance of the first lesion. Primary skin lesions ranged from 1-3 in number, and all had the aspect of an erythematous, infiltrated plaque, variously located on the head, arms or legs. There was lymphatic dissemination of infection, with lymph node enlargement in seven of the cases, and the delayed hypersensitivity skin-test (DTH) was negative in all eight patients prior to their treatment. After that, there was a conversion of DTH to positive in five cases re-examined. The major histopathological feature was a dermal mononuclear infiltration, with a predominance of heavily parasitized and vacuolated macrophages, together with lymphocytes and plasma cells. In one case, with similar histopathology, the patient had acquired his infection seven years previously and he presented with the largest number of disseminated cutaneous lesions. BDCL shows clinical and histopathological features which are different from those of both LCL and ADCL, and there is a good prognosis of cure which is generally not so in the case of frank ADCL.